2012
DOI: 10.7202/1012540ar
|View full text |Cite
|
Sign up to set email alerts
|

Le rôle des conditions de travail dans la satisfaction et la loyauté des infirmières d’agence au Québec

Abstract: Depuis les dernières années, l’attrait des infirmières pour les agences de placement temporaire a connu une croissance marquée. Or, dans un contexte de rareté de la main-d’oeuvre, on peut se demander quelles sont les sources de motivation qui incitent les infirmières à choisir le travail d’intérim et à demeurer loyales envers leur agence. Prenant appui sur la classification de Tan et Tan (2002), quatre sources de motivations ont été explorées, soit les motivations individuell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 69 publications
(49 reference statements)
0
5
0
4
Order By: Relevance
“…This led to extensive reliance on healthcare personnel contracted at high cost from private agencies. 42 Union leaders voiced their longstanding concerns around working conditions:…”
Section: Sector Integrationmentioning
confidence: 99%
“…This led to extensive reliance on healthcare personnel contracted at high cost from private agencies. 42 Union leaders voiced their longstanding concerns around working conditions:…”
Section: Sector Integrationmentioning
confidence: 99%
“…In the United States, specifically in New York State, the predominance of low-wage jobs and low educational levels in the projection of the healthcare workforce is diagnosed as a result of economic pressure on the healthcare industry to use the workforce more efficiently and effectively (28) . In Canada, an article discussed the growing presence of temporary employment agencies in the context of job scarcity and how professionals are dissatisfied with this form of employment (29) . In France, we located a publication on unemployment and poor working conditions in a survey conducted by the national federation of nursing students, which found that 14% of new graduates are looking for jobs, whereas 44% are working under non-extended, part-time work arrangements (30) .…”
Section: Discussion Hospitals As Cores Of a Subcontracted Services Nementioning
confidence: 99%
“…Singh and Loncar (2010) examine the relation among satisfaction with wage, satisfaction with employment, and change of employment. Tremblay et al (2012) demonstrate that family motivation and professional development motivation have positive effects on satisfaction; good economic conditions are not enough.…”
Section: Influence Of Job Features On Job Satisfactionmentioning
confidence: 97%